Estimation of Dioxins in Workers Collecting and Burning of Waste - Hamid J. Mohammad (Journal of Global Pharma Technology, 2016)
The study included measuring the concentration 17 congeners from PCDD/Fs (7 PCDDs and 10 PCDFs) in the blood lipids of workers collecting and burning of waste for 56 candidates, the range of age was 23–42 years, classified into two categories depending on the period of exposure. The first category (category 2) includes 27 persons, the exposure period was <10 years, the mean age was 30.3±3.5 years, the mean PCDDs, PCDFs and PCDD/Fs were 8.61, 5.34 and 13.95 (pg WHO–TEQ/g lipid), respectively. The second category (category3) includes 29 persons, the exposure period was >10 years. The mean age was 35.6±2.8 years, the mean PCDDs, PCDFs and PCDD/Fs were 9.89, 5.65 and 15.54 (pg WHO–TEQ/g lipid), respectively. The data were compared with a control group (category1) (general (non-exposed) populations) including 50 candidates; the mean age was 32.2± 2.6 years, the mean PCDDs, PCDFs and PCDD/Fs were 6.87, 3.38 and 10.25 (pg WHO–TEQ/g lipid), respectively. A probability of 0.05.Keywords: PCDD/Fs, Burning of waste, Polychlorinated dibenzodioxins, Polychlorinated dibenzofurans.